2013
DOI: 10.1111/pme.12156
|View full text |Cite
|
Sign up to set email alerts
|

A Cross-Sectional Exploratory Survey of Knowledge, Attitudes and Daily Self-Reported Pain Assessment Practice among Nurses in Mainland China

Abstract: Aims and Objectives. To describe the level of knowledge, attitudes, and self-reported quality of practice in pain assessment among nurses of Mainland China and explore links with current hospital pain policy and continuing education.Background. Knowledge is necessary for skilled pain assessment among nurses. Little is currently known regarding knowledge, attitude toward, and self reported pain assessment by nurses from Mainland China.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 28 publications
(36 reference statements)
0
5
1
Order By: Relevance
“… 7 A domestic survey of nurses in 76 hospitals between 2011 and 2012 found that as many as 71.2% of the surveyed nurses did not focus on the effect of pain on the functional activity of patients. 11 The same survey revealed that 57.1% of the hospitals assessed pain as the fifth vital sign, and 47% assessed the pain at rest and activity. In recent years, with the issuance of detailed rules for hospital accreditation, particularly the issuance of the guidelines regarding acute pain, has resulted in an increased focus by hospitals on pain management.…”
Section: Discussionmentioning
confidence: 99%
“… 7 A domestic survey of nurses in 76 hospitals between 2011 and 2012 found that as many as 71.2% of the surveyed nurses did not focus on the effect of pain on the functional activity of patients. 11 The same survey revealed that 57.1% of the hospitals assessed pain as the fifth vital sign, and 47% assessed the pain at rest and activity. In recent years, with the issuance of detailed rules for hospital accreditation, particularly the issuance of the guidelines regarding acute pain, has resulted in an increased focus by hospitals on pain management.…”
Section: Discussionmentioning
confidence: 99%
“…According to previous experience, education, timely assessment of pain and optimization of analgesic techniques, were beneficial for increasing patients' compliance and analgesic efficacy in Chinese patients. [ 28 29 ] Taking postoperative pain as an example, currently, postoperative analgesia was mainly provided by anesthesiologists, yet, how surgeons evaluate and practice pain management also impacted on postoperative pain. If surgeons only administered analgesics according to the request of patients in a fixed pattern, inadequacy in dosages of analgesic medications or potency could prolong the duration of severe pain and associated adverse events.…”
Section: Discussionmentioning
confidence: 99%
“…The Knowledge and Attitudes Survey Regarding Pain (KASRP) was developed in 1987 and has been used extensively and revised over the years to reflect changes in pain management practice (Ferrell & McCaffery, ). The KASRP revised in 2008 was translated into Chinese (Ying Ge et al., ) and used in this study. It consists of 40 questions, 22 true/false questions, 14 multiple choice questions and 4 questions pertaining to two case studies.…”
Section: Methodsmentioning
confidence: 99%
“…One point was given for each correct answer, and the final score was calculated as a percentage of the total questions. Content validity, test–retest reliability and internal consistency reliability of the Chinese version of KASRP were acceptable (Ying Ge et al., ). Information about nurses’ demographics, previous attendance in continuing education on pain, and self‐report of using pain assessment tools were also collected.…”
Section: Methodsmentioning
confidence: 99%